Answer: Average annual salary of the 3 people is equal to Kate's annual salary.
Step-by-step explanation:
Since we have given that
Difference between Mary's and Jim's annual salaries be m-j
Difference between Mary's and Kate's annual salaries be m-k
According to question, we get that
[tex]m-j=2(m-k)\\\\m-j=2m-2k\\\\2k-j=2m\\\\2k-j=m[/tex]
Average annual salary of the 3 people would be
[tex]\dfrac{m+k+j}{3}\\\\=\dfrac{2k-j+j+k}{3}\\\\=\dfrac{3k}{3}\\\\=k[/tex]
Hence, average annual salary of the 3 people is equal to Kate's annual salary.